Microeconomics / Ralph T Byrns; Gerald W Stone - Byrns, Ralph T.
A standard introductory textbook that has been well honed over time. This updated edition adds a new chapter on the economics of health care, and new information on the globalization of economic activity, the dynamics of labor markets, and the pervasiveness of imperfect information and strategic be